Emotional distress and the quality of life for teachers during the pandemic - Sandu, Mihaela; Marin, Mihaela Veronica; Rus, Ciprian-Vasile (Technium Social Sciences Journal, 2022)
This paper presents the synthesis of some investigations presented in literature, on the emotional distress and the quality of life of teachers during the pandemic, as well as the results of personal research, through which I set out to investigate the well-being of teachers and the outcome the pandemic had upon them.As many authors have shown, the pandemic is associated with many physical and mental states, having repercussions on the personality and lifestyle of teachers, turning their lives upside down. The effects of the Covid-19 pandemic are felt on every level of the teachers’ personalities, such as: changes in the system of interests and values, manifest behaviors, degradation of the nature of the image, and self-esteem.